Effects of Salmon Ingestion on Post-Exercise Muscle Protein Synthesis: Exploration of Whole Protein Foods Versus Isolated Nutrients - Paulussen, Kevin (Curr Dev Nutr, 2020)
OBJECTIVES: Healthy eating patterns consist of eating whole foods as opposed to single nutrients. The maintenance of skeletal muscle mass is of particular interest to overall health. As such, there is a need to underpin the role of eating nutrients within their natural whole-food matrix versus isolated nutrients on the regulation of postprandial muscle protein synthesis rates. This study assessed the effects of eating salmon, a potential food within a healthy Mediterranean style eating pattern, on the stimulation of post-exercise muscle protein synthesis rates versus eating these same nutrients in isolation in healthy young adults. METHODS: In a crossover design, 10 recreationally active adults (24 ± 4 y; 5 M, 5 F) performed an acute bout of resistance exercise followed by the ingestion of salmon (SAL) (20.5 g protein and 7.5 g fat) or its matched constituents in the form of crystalline amino acids and fish oil (ISO). Blood and muscle biopsies were collected at rest and after exercise at 2 and 5 h during primed continuous infusions of L-[ring-(2)H(5)]phenylalanine for the measurement of myofibrillar protein synthesis and plasma amino acid profiles. Data were analyzed by using a 2-factor (time × condition) repeated-measures ANOVA with Tukey's post hoc test. RESULTS: Plasma essential amino acid concentrations increased to a similar extent in both SAL and ISO during the postprandial period (P > 0.05). Likewise, postprandial plasma leucine concentrations did not differ between nutrient condition (P > 0.05). The post-exercise myofibrillar protein synthetic responses were similarly stimulated in both nutrition conditions early (0–2 h; 0.079 ± 0.039%/h (SAL) compared to 0.071 ± 0.078%/h (ISO); P = 0.64) and returned to baseline later (2–5 h; 0.046 ± 0.020%/h (SAL) compared to 0.038 ± 0.025%/h (ISO); P = 0.90). Similarly, there were no differences in the stimulation of myofibrillar protein synthesis rates between SAL and ISO during the entire 0–5 h recovery period (0.058 ± 0.024%/h compared to 0.045 ± 0.027%/h, respectively; P = 0.66). CONCLUSIONS: We show that the ingestion of salmon or its isolated nutrients increases plasma amino acid concentrations and enhances the stimulation of post-exercise muscle protein synthesis rates with no differences in the temporal or cumulative responses in healthy young adults. FUNDING SOURCES: USDA National Institute of Food and Agriculture Hatch project.